IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KREATIF LAPANGAN: IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KREATIF LAPANGAN - Indah Liana Hutabalian (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2020)
The focus of this study is the implementation of the policy of structuring the creative field of study traders at Jl. Yos Sudarso Ujung. The objectives of this research are two things, first, see how the implementation of the Field Creative Merchant arrangement policy at Sangomang Single Culinary Park on Jl. Yos Sudarso Ujung. Second, find out what are the supporting and inhibiting factors in achieving the implementation of the Field Creative Merchant arrangement policy at the Sangomang Single Culinary Park on Jl. Yos Sudarso Ujung. The research method used in this research is descriptive qualitative method. This method is used to provide an overview of the Implementation of the Field Creative Merchant Arrangement Policy Study on the Sangomang Single Culinary Park at Jl. Yos Sudarso Ujung. The focus of the research is based on Van Mettern and Varn Horn theory which is influenced by six variables, namely policy size and objectives, resources, characteristics of executing agents, dispositions of disposing agents, communication between organizations and implementing activities, social, economic and political environment. The data obtained is based on information from the Head of the City Planning and Aesthetics Division at the Public Housing Service and Palangka Raya City Settlement Area, UPT Pasar Kahayan Staff and the Creative Field Merchant community. Data collection techniques in the form of observations, interviews and documentation. Besides that, the data analysis techniques are in the form of data reduction, data presentation, and conclusion / verification. The research results on the implementation of street vendor arrangement policies in Jl. Yos Sudarso Ujung has not been carried out optimally, this happened because the human resources managing the street vendor arrangement were still inadequate as well as the absence of a special division that managed the street vendor arrangement so that the street vendor arrangement policy was carried out by the Public Housing and Palangka Raya Housing Area during this hasn't gone well.